A photochromic metallacycle with highly anisotropic Dy–F magnetic units. Issue 35 (14th April 2023) - El Beyrouti, Nour; Houard, Felix; Cordier, Marie; Trzop, Elzbieta; Rigaut, Stéphane; Le Guennic, Boris; Bernot, Kevin; Norel, Lucie
Abstract : A dinuclear metallacycle assembled from a bispyridyl dithienylethene linker and a highly anisotropic dysprosium based Single Molecule Magnet (SMM) shows magnetic hysteresis at 1.8 K together with photoisomerization in single crystals. Abstract : A dinuclear metallacycle assembled from a bispyridyl dithienylethene linker and a highly anisotropic dysprosium based Single Molecule Magnet (SMM) shows magnetic hysteresis at 1.8 K together with photoisomerization in single crystals (SC). The impact of photoswitching on the SMM behavior is evidenced and related to the specific organization of the magnetic units.